2008
DOI: 10.2174/157340308784245810
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of the Ankle Brachial Index

Abstract: Ankle brachial index (ABI) has been utilized in the management of peripheral arterial disease (PAD).ABI is a surrogate marker of atherosclerosis and recent studies indicate its utility as a predictor of future cardiovascular disease and all-cause mortality. Even so, this critical test is underutilized. The purpose of this review is to summarize available evidence associated with ABI methodology variances, ABI usage in the treatment of PAD, and ABI efficacy in predicting cardiovascular disease. This review furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 51 publications
1
63
0
6
Order By: Relevance
“…For each leg, the higher of the BP values in the dorsalis pedis and posterior tibial arteries was divided by the higher of the left and right arm brachial BP values, and the lower of the two results (right and left leg) was used as ABI in all analyses [19]. The presence of PAD was defined by an ABI 0.9 [3,20].…”
Section: Abi Measurementmentioning
confidence: 99%
“…For each leg, the higher of the BP values in the dorsalis pedis and posterior tibial arteries was divided by the higher of the left and right arm brachial BP values, and the lower of the two results (right and left leg) was used as ABI in all analyses [19]. The presence of PAD was defined by an ABI 0.9 [3,20].…”
Section: Abi Measurementmentioning
confidence: 99%
“…Additionally, lower ABI values correlated with reduced survival and increased rate of concomitant coronary and cerebrovascular disease 38 . Despite a very high incidence of MACE and mortality rate, PAD is still underdiagnosed and undertreated.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, there has been a lack of attention to PAD despite availability of screening tools and the contribution to adverse health outcomes [11,20,21,[47][48][49]. This emphasises the need for increasing the focus of PAD as an important comorbidity, tailoring multidisciplinary approach to the prevention, treatment and management of PAD and supporting individuals in selfmanagement approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the review concluded that the ABI is a simple and convenient tool with high specificity and accuracy for the preliminary diagnosis of PAD in populations aged between 40 and 75 years with at least one vascular risk factor, a profile that is typical of most patients with CHF [20]. Since measurement of the ABI is an effective screening tool in both symptomatic and asymptomatic PAD, standardised screening practices may improve the detection of PAD in patients with CHF [21], thereby allowing targeting and tailoring of chronic disease management interventions.…”
Section: Introductionmentioning
confidence: 99%